1990
DOI: 10.1055/s-0038-1634798
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of ECG Interpretation in the Dalhousie Program; NOVACODE ECG Classification Procedures for Clinical Trials and Population Health Surveys

Abstract: The Dalhousie ECG Program was designed specifically for the needs of epidemiologic studies, health surveys, and clinical trials. The program logic is dynamic in that it can accommodate any combination of ECG leads, record length and sampling rate. The NOVACODE module of the program classifies ECGs according to the Minnesota Code, supplemented with new sets of logic criteria for conduction defects, acute myocardial infarction, and serial ECG changes. Improved statistical models are incorporated for enhanced det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(86 citation statements)
references
References 23 publications
0
86
0
Order By: Relevance
“…They also did not use a prediction equation for FEV 1 to adjust for differences in age, sex, height, and race of study participants, which could have led to residual confounding by these variables. 17 More importantly, the study by Cirillo et al 27 did not evaluate the role of airflow obstruction (or its severity) on systemic inflammation. We have extended the findings of Cirillo et al 27 and have shown that moderate to severe (but not mild) COPD is strongly associated with systemic low-grade inflammation and ECG evidence of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also did not use a prediction equation for FEV 1 to adjust for differences in age, sex, height, and race of study participants, which could have led to residual confounding by these variables. 17 More importantly, the study by Cirillo et al 27 did not evaluate the role of airflow obstruction (or its severity) on systemic inflammation. We have extended the findings of Cirillo et al 27 and have shown that moderate to severe (but not mild) COPD is strongly associated with systemic low-grade inflammation and ECG evidence of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…17 NOVACODE ECG classification procedures were used to estimate left ventricular mass index of study participants. 17 Left ventricular mass indexes of Ͼ150 g/m 2 for men and Ͼ120 g/m 2 for women were used as cutoff points to define left ventricular hypertrophy. 15 …”
Section: Spirometry and Electrocardiographymentioning
confidence: 99%
“…3 All ECGs were processed in a central laboratory (EPICARE Center, Wake Forest University, NC), and they were all visually inspected for technical errors and inadequate quality. ECGs were initially processed by the Dalhousie ECG program, 4 and processing was later repeated for the present study by the 2001 version of the Marquette 12-SL program (GE Marquette). The variables of key interest considered as initial candidates for risk prediction included some ECG waveform descriptors derived by the Novacode program.…”
Section: Ecg Methodologymentioning
confidence: 99%
“…A 10-s segment of simultaneous ECG leads was sampled at a rate of 250 samples/s. ECGs were transmitted daily to the Epidemiological Cardiology Research Center (WinstonSalem, NC) for analysis and classification using the Minnesota code derived from the NOVACODE ECG program (17,18). Multiple editing removed poor quality tracings.…”
Section: Measurementsmentioning
confidence: 99%